PENGARUH PERMAINAN TRADISONAL PETAK JONGKOK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK PERTIWI DESA TERATE KECAMATAN SIRAH PULAU PADANG OKI - Lestari, Widya; Fahmi, Fahmi; Cindrya, Elsa; Fitri, Izza (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this study was to determine the effect of traditional games of squatting on gross motor skills of children aged 5-6 years. The research method is the Experimental Method with the type of Pre-Experimental Designs with the design One Group Pretest-Posttes Designs. The population of this study were group B children totaling 13 people. The observation is group B children aged 5-6 years. The results of the research and discussion are that there is an increase in gross motor skills in children, it can be said that in this study there is a significant effect given the traditional game activities of squatting plots, this is shown in the experimental post-test using relay games. Before the application of squatting traditional game activities, children with low gross motor skills were 6 children, while the medium value was 7 children. After applying the traditional game activities of squatting plots, the value of children's gross motor skills is very good 2 people and motor skills develop as expected there are 6 children, and the value starts to develop only 5 children, which means that after being given treatment, children's gross motor skills increase than before treatment, and these activities improve the gross motor skills of early childhood.